Mesospheric tide comparisons at low latitudes observed by two collocated meteor radars - Jian Li; Wen Yi; XiangHui Xue; Jie Zeng; HaiLun Ye; JianYuan Wang; JinSong Chen; Na Li; TingDi Chen (Earth and Planetary Physics)
Accurate knowledge of mesospheric winds and waves is essential for studying the dynamics and climate in the mesosphere and lower thermosphere (MLT) region. In this study, we conduct a comparative analysis of the mesosphere tidal results obtained from two adjacent meteor radars at low latitudes in Kunming, China, from November 2013 to December 2014. These two radars operate at different frequencies of 37.5 MHz and 53.1 MHz, respectively. However, overall good agreement is observed between the two radars in terms of horizontal winds and tide observations. The results show that the dominant tidal waves of the zonal and meridional winds are diurnal and semidiurnal tides. Moreover, we conduct an exhaustive statistical analysis to compare the tidal amplitudes and vertical wavelengths recorded by the dual radar systems, which reveals a high degree of alignment in tidal dynamics. The investigation includes variances and covariances of tidal amplitudes, which demonstrate remarkable consistency across measurements from both radars. This finding highlights clear uniformity in the mesospheric tidal patterns observed at low latitudes by the two neighboring meteor radars. Results of the comparative analysis specifically underscore the significant correlation in vertical wavelength measurements, validating the robustness of radar observations for tidal research.